Cut - McCormick, Patricia, 1956- (New York : Scholastic, 2002)
While confined to a mental hospital, thirteen-year-old Callie slowly comes to understand some of the reasons behind her self-mutilation, and gradually starts to get better.
660
Keywords: Self-mutilation -- Juvenile fiction; Teenage girls -- Juvenile fiction; Psychiatric hospitals -- Juvenile fiction